Low-wage jobs, foreign-born workers, and firm performance - Catalina Amuedo Dorantes; Esther Arenas-Arroyo; Parag Mahajan; Bernhard Schmidpeter (Johannes Kepler University of Linz, Department of Economics, 2023)
We examine how migrant workers impact firm performance using administrative data from the United States. Exploiting an unexpected change in firms' likelihood of securing low-wage workers through the H-2B visa program, we find limited crowd-out of other forms of employment and no impact on average pay at the firm. Yet, access to H-2B workers raises firms' annual revenues and survival likelihood. Our results are consistent with the notion that guest worker programs can help address labor shortages without inflicting large losses on incumbent workers.
Keywords: J23; F22; J61; 330; guest workers; migrants; employment; firm dynamics; H-2B visa